Determining tourism value of National Park of Urmia Lake in Iran by family production function - Ali Bagherzadeh (UTMS Journal of Economics, 2012)
According to the importance of environmental resources in preserving natural ecosystems and human life, preserving these resources and preventing their destruction is necessary. National Park of Urmia Lake in West Azarbayjan province of Iran is the settlement of rare species for different animals and herbs. Every year a lot of internal and foreign passengers and tourists visit this national Park, so the purpose of this study is recreation demand function derivation in National Park of Urmia Lake and determining social and economic factors on demand function. So we used travel cost pattern within the frame work of family production function. Optimal sample volume was 75 tourists and data is related to 2010 summer. Results showed recreation demand function has positive relation with tourists income, quality of National Park and visitor's education, also it has negative relation with recreation shadow price that is according to theoretical expectations. So, quality improvement of National Park as an effective key factor on recreation demand and using suitable pricing policy are recommended.
Keywords: Q51; Q56; 330; family production function; recreation demand function; econometric methods; National Park of Urmia Lake